Behavioral Alterations Caused by Pain and Inflammation in Rodent Models (Bangladesh Pharmaceutical Journal, 2024)
The aim of the current study is to examine the impact of pain and inflammation on CNS behavior in rodent models.  Test mice were segmented into a control group and two test groups, group 1 and group 2. 0.7% 1 mL acetic acid per mice was used for pain induction whereas inflammation was induced using 0.2 mL 1% carrageenan per mouse. The results demonstrated after pain induction, the test group writhes an average of 18.5 and 16 times/15 minute while no writhing in control group, indicating successful pain induction in test group. A 38.88% and 52.94% increased paw volume was observed after 30 minutes of carrageenan induction in test group 1 and 2 respectively. Both pain induced group 1 and 2 showed 79% and 78% lowered head dipping while 62% and 57% lowered head dipping was observed among test group 1 and 2 with inflammation in Hole board test. Reduced mobility time was observed from tail suspension test. Pain induced and inflammation induced test groups 1 and 2 showed 29% and 14% as well as 28.19% and 15.14% reduction in mobility time respectively. Similarly test group 1 and 2 enduring pains demonstrated 50% and 35% less exploration to the open arm whereas 75% and 89% lower exploration to the open arm was exhibited by the test group 1 and 2 with persuaded inflammation respectively in elevated plus maze test. All these results of behavioral tests suggested that both test groups had reduced CNS activity which possibly due to the induced inflammation and pain.Bangladesh Pharmaceutical Journal 27(2): 201-206, 2024 (July)